Refugia and anthelmintic resistance: Concepts and challenges. (August 2019) - Hodgkinson, Jane E.; Kaplan, Ray M.; Kenyon, Fiona; Morgan, Eric R.; Park, Andrew W.; Paterson, Steve; Babayan, Simon A.; Beesley, Nicola J.; Britton, Collette; Chaudhry, Umer; Doyle, Stephen R.; Ezenwa, Vanessa O.; et al.
Abstract: Anthelmintic resistance is a threat to global food security. In order to alleviate the selection pressure for resistance and maintain drug efficacy, management strategies increasingly aim to preserve a proportion of the parasite population in 'refugia', unexposed to treatment. While persuasive in its logic, and widely advocated as best practice, evidence for the ability of refugia-based approaches to slow the development of drug resistance in parasitic helminths is currently limited. Moreover, the conditions needed for refugia to work, or how transferable those are between parasite-host systems, are not known. This review, born of an international workshop, seeks to deconstruct the concept of refugia and examine its assumptions and applicability in different situations. We conclude that factors potentially important to refugia, such as the fitness cost of drug resistance, the degree of mixing between parasite sub-populations selected through treatment or not, and the impact of parasite life-history, genetics and environment on the population dynamics of resistance, vary widely between systems. The success of attempts to generate refugia to limit anthelmintic drug resistance are therefore likely to be highly dependent on the system in hand. Additional research is needed on the concept of refugia and the underlying principles for its application across systems, as well as empirical studies within systems that prove and optimise its usefulness. Graphical abstract: Image 1 Highlights: Refugia is currently recommended for strategic control of AR in GI nematodes of livestock. Conditions required for refugia-based control may differ between parasite systems. An improved understanding of the parameters influencing refugia-based control is required.